Directional biases for blink adaptation in voluntary and reflexive eye blinks - Lau, Wee Kiat (2020)
The oculomotor system is subject to noise, and adaptive processes compensate for consistent errors in gaze targeting. Recent evidence suggests that positional errors induced by eye blinks are also corrected by an adaptive process: When a fixation target is displaced during repeated blinks, subsequent blinks are accompanied by an automatic compensating eye movement anticipating the updated target location after the blink. Here, we further tested the extent of this "blink adaptation." Participants were tasked to look at a white target dot on a black screen and encouraged to blink voluntarily, or air puffs were used to elicit reflexive blinks. In separate runs, the target was displaced by 0.7° in either of the four cardinal directions during blinks. Participants adapted to positional changes during blinks, i.e., the postblink gaze position was biased in the direction of the dot displacement. Adaptation occurred for both voluntary and reflexive blinks. However, adaptation was unequal across different adaptation directions: Horizontally, temporal displacements experienced larger adaptation than nasal displacements; vertically, downward displacements led to larger adaptation than upward displacements. Results paralleled anisotropies commonly found for saccade amplitudes, and thus it is likely that gaze corrections across eye blinks share general constraints of the oculomotor system with saccades.